Low cytomegalovirus seroprevalence in early multiple sclerosis: a case for the 'hygiene hypothesis'?. (15th April 2018) - Alari‐Pahissa, E.; Moreira, A.; Zabalza, A.; Alvarez‐Lafuente, R.; Munteis, E.; Vera, A.; Arroyo, R.; Alvarez‐Cermeño, J. C.; Villar, L. M.; López‐Botet, M.; Martínez‐Rodríguez, J. E.
Abstract : Background and purpose: Cytomegalovirus (CMV) infection has recently been associated with a lower multiple sclerosis (MS) susceptibility, although it remains controversial whether it has a protective role or is merely an epiphenomenon related to westernization and early‐life viral infections. We aimed to evaluate whether CMV serostatus may differ in patients with early MS as compared with patients with non‐early MS, analyzing the putative association of this virus with MS clinical course and humoral immune responses against other herpesviruses. Methods: Multicentric analysis was undertaken of 310 patients with MS (early MS, disease duration ≤5 years, n  = 127) and controls ( n  = 155), evaluating specific humoral responses to CMV, Epstein–Barr virus and human herpesvirus‐6, as well as T‐cell and natural killer (NK)‐cell immunophenotypes. Results: Cytomegalovirus seroprevalence in early MS was lower than in non‐early MS or controls ( P  < 0.01), being independently associated with disease duration (odds ratio, 1.04; 95% confidence interval, 1.01–1.08, P  < 0.05). CMV+ patients with MS displayed increased proportions of differentiated T‐cells (CD27−CD28−, CD57+, LILRB1+) and NKG2C+ NK‐cells, which were associated with a lower disability in early MS ( P  < 0.05). CMV+ patients with early MS had an age‐related decline in serum anti‐EBNA‐1 antibodies ( P  < 0.01), but no CMV‐related differences in anti‐human herpesvirus‐6 humoral responses. Conclusions: Low CMV seroprevalence was observed in patients with early MS. Modification of MS risk attributed to CMV might be related to the induction of differentiated T‐cell and NK‐cell subsets and/or modulation of Epstein–Barr virus‐specific immune responses at early stages of the disease.